A promising binary nanocomposite of zinc cobaltite intercalated with polyaniline for supercapacitor and hydrazine sensor - Omar, F.S.; Numan, A.; Duraisamy, N.; Bashir, S.; Ramesh, K.; Ramesh, S. (Elsevier, 2017)
Herein, zinc cobaltite (ZnCo2O4) nanoparticles (synthesized via hydrothermal treatment) were blended with polyaniline (PANI) (synthesized via chemical oxidative polymerization) to form PANI-ZnCo2O4 nanocomposite. The structural crystallinity and phase purity of PANI-ZnCo2O4 nanocomposite were authenticated by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) analysis. The morphological studies showed that the spinel structured ZnCo2O4 nanoparticles were well embedded on tubular-shaped PANI matrix, suggesting the effective connection between ZnCo2O4 nanoparticles with PANI matrix. The electrochemical performance studies of PANI-ZnCo2O4 nanocomposite for supercapacitor exhibited enhanced specific capacity of 398 C/g at a current density of 1 A/g as compared with ZnCo2O4 nanoparticles and PANI. The enhancement of electrochemical performance was contributed from the augmentation of electroactive sites for redox reaction, rapid electron transfer rate and the synergistic effect of ZnCo2O4 nanoparticles and highly conductive PANI. The fabricated PANI-ZnCo2O4//activated carbon based hybrid supercapacitor achieved high energy density (13.25 Wh/kg at 375 W/kg) as well as excellent cycling stability (∼90% retention after 3000 cycles). Furthermore, PANI-ZnCo2O4 nanocomposite was employed as a hydrazine sensor which exhibited good sensitivity of 0.43 μA μM−1 in the linear range of 0.1–0.6 mM with a low detection limit of 0.2 μM.